Clinical management of sickle cell liver disease in children and young adults. Issue 4 (11th November 2020) - Kyrana, Eirini; Rees, David; Lacaille, Florence; Fitzpatrick, Emer; Davenport, Mark; Heaton, Nigel; Height, Sue; Samyn, Marianne; Mavilio, Fulvio; Brousse, Valentine; Suddle, Abid; Chakravorty, Subarna; et al.
Abstract : Liver involvement in sickle cell disease (SCD) is often referred to as sickle cell hepatopathy (SCH) and is a complication of SCD which may be associated with significant mortality. This review is based on a round-table workshop between paediatric and adult hepatologists and haematologists and review of the literature. The discussion was prompted by the lack of substantial data and guidance in managing these sometimes very challenging cases. This review provides a structured approach for the diagnosis and management of SCH in children and young adults. The term SCH describes any hepatobiliary dysfunction in the context of SCD. Diagnosis and management of biliary complications, acute hepatic crisis, acute hepatic sequestration and other manifestations of SCH are discussed, as well as the role of liver transplantation and haemopoietic stem cell transplantation in the management of SCH.